Clinical Indications of Panchatikta Kashaya An Experiential And Scientific View - Shripathi , Acharya G; Acharya, Miss Rajeshwari S (International Research Journal of Ayurveda & Yoga, 2021)
Herbal formulations are commonly prescribed by Ayurveda physicians. They are having least side effects. Kashaya is one such preparation which has water soluble extracts of multiple herbal ingredients. Panchatikta kashaya is a decoction of five bitter herbs – Guduchi(Tinosporia cordifolia) , Vasaka( Adhatoda vasica), Katuki (Picrorhiza kurroa), Bhunimba (Andrographis paniculata) and Nimba twak (Azadirachta indica). These drugs are having tikta rasa (bitter taste), laghu (light) rooksha(rough) guna, dipana(appetizer) , pachana(digestives) , pittahara , krimighna (killing of worms / parasites), raktashodhska (blood purifier) and kaphapitta nashaka action. It is indicated in Kasa(cough), Shwasa(bronchial asthma), Jwara(fever), Krimi(worms), madhumeha (diabetes), kushtha(skin diseases), sthoulya(obesity) , Vatarakta and pittaja disorders . Panchatikta kashaya can be given in multiple diseases with suitable adjuvant Ayurveda formulations which are disease specific in action. The present paper highlights about the clinical indications of Panchatikta kashaya in a scientific and experiential view.